Profile of patients with newly diagnosed HIV in the Łódź region in Poland from 1996 to 2005 - Jabłonowska, Elżbieta; Małolepsza, Ewa (Archives of Medical Science, 2009)
Introduction: To determine whether the profile of patients diagnosed with HIV changed during the years 1996-2005. Material and methods: Data from 407 patients diagnosed with HIV between 1996 and 2005 were collected and retrospectively analyzed. The patients were grouped according to the year in which they were diagnosed with HIV. The age, gender, route of transmission, CD4 lymphocyte count, clinical evaluation according to CDC, and presence of anti-HCV and HBsAg antigen were assessed at the time of diagnosis. Each group of parameters was compared according to the year in which the HIV infection was detected. Results: The group consisted of 407 patients: 291 men and 116 women. Men represent a larger proportion in each of the studied periods. The patients’ average age was 28.31 and was comparable in the individual years. The average level of CD4 lymphocytes in the entire group was 427.73 cells/mm3, and a change in the trend of their count was not observed over the years, although statistically significant differences were seen between the years (1996-1998, 1996-2004, 1998-2004, 2001-2004). In 2004, as many as 20.5% of the patients were simultaneously diagnosed with HIV and AIDS. In all of the studied periods, the use of intravenous drugs was the main route of transmission. It should be emphasized that, in 2005, the decrease in the percentage of such exposures was statistically significant. In the same year, there was also a statistically significant reduction in the number of patients in whom anti-HCV was detected (a statistically significant change compared to the results obtained during the other years). A significant difference in the frequency of anti-HBsAg was not observed over the years. Conclusions: We did not observe a stable trend of change in the profiles of newly diagnosed patients, in our region, despite some periodic differences. In 2005, a statistically significant decrease in the number of infections caused by intravenous drug use was observed. This drop had a substantial effect on the frequency of HCV co-infection.